Assessing Fertility Knowledge Among Obstetrics and Gynecology Residents: A Multicenter Cross-Sectional Study - Hemasa Gul; Nabila Khan; Naila; Fatima; Huma Gul (Pakistan Journal of Medicine and Dentistry, 2025)
Background: Fertility knowledge is essential for obstetrics and gynecology residents, yet gaps in understanding key reproductive health concepts persist. The study aimed to investigate the extent of fertility-related knowledge among obstetrics and gynecology residents and analyze associated demographic and training factors.